PENGARUH METODE TGT TERHADAP KETERAMPILAN HEADING PESERTA DIDIK SMP NEGERI 11 SUNGAI RAYA - Arpandi, Arpandi; Hidasari, Fitri Puspa; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem taken by this study is whether there is an influence of Team Games Tournament on the heading skills of students of Sungai Raya 11 Middle School. The purpose of this study was to determine the effect of Team Games Tournament on the heading skills of students at Sungai raya 11 Middle School. The research method used in this study is in the form of one group pretest and posttest design. the study population were participants of the Sungai Raya 11 Middle School students. The number of samples in this study amounted to 14 students. Where students are given treatment to do variations of the given heading game. The results of the analysis show that there is a significant effect on the variation of heading games based on Team Game Tournament (TGT) to improve heading skills in students of Sungai Negeri 11 Middle School. From the t test it can be seen that the results of T-count> T-table: 1.86> 1.771, and a percentage increase of 57%. With this conclusion, it can be concluded that there is an influence on the variation of Team Game Tournament (TGT) based headings to improve students' heading skills..Keyword: Team Games Turnament, Heading